Implementation of Character Education in Elementary Schools in Indonesia and Malaysia - et. al., Aan Komariah, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to describe the implementation of character education in elementary schools. The research method used survey by distributing questionnaires by Google form which then were analyzed descriptively and quantitatively. These questionnaires were distributed to principals and teachers in elementary schools in Indonesia and Malaysia. Results of the research show that the implementation of character education consisting of initial assessment of character education implementation, vision, socialization of strengthening character education implementation, mission and formulation of strengthening character education, policy design of strengthening character education, program design of strengthening character education, implementation of strengthening character education, evaluation of strengthening character education program implementation which has been implemented by different values in Indonesia and Malaysia. By this research, it is expected that there will be an illustration on the implementation of strengthening character education which can be used as a reference so there will be superior schools and ones encouraging the presence of characterized students.